The benefits of an unsupervised exercise program in persons with well-healed burn injuries within the International Classification of Functioning, Disability and Health (ICF) - Huang, Mu; Moralez, Gilbert; Romero, Steven A.; Jaffery, Manall F.; Cramer, Matthew N.; Petric, Jan Karel; Nabasny, Andrew D.; Crandall, Craig G. (Burns, 2020)
•An unsupervised exercise training program is beneficial in the long-term rehabilitation of individuals with burn injuries.•Unsupervised exercise training improves strength and activity limitations in burn-injured individuals equal to uninjured counterparts.•Improvements made in lower extremity strength and functional activities can be achieved regardless of the severity of burn injury. Vast improvements in the survival rates following burn injuries has led to a greater number of patients living with a wide range of long-term impairments, activity limitations, and participation constraints. Therefore, long-term care is critical in this clinical population and necessitates appropriate rehabilitation strategies to maximize an individual’s overall health. The purpose of this study was to test the hypothesis that the extent to which outcomes within the International Classification of Functioning, Disability, and Health (ICF) framework are improved following 6 months of unsupervised exercise training is influenced by the severity of a burn injury (i.e., percent body surface area injured). Outcome variables representing the dimensions of the ICF, body functions & structure, activity, and participation, were collected pre- and post- 6 months of exercise training in three groups of participants: non-injured control subjects (N = 11), subjects with moderate-level well-healed burn injuries (N = 13, 26 ± 6% body surface area burned), and subjects with high-level well-healed burn injuries (N = 20, 58 ± 15% body surface area burned). Exercise training improved lower extremity strength (changes in peak torque/kg body mass at 90 degrees/sec flexion: 30 ± 5% and extension: 36 ± 4%, p < 0.05) and functional activities (changes in sit to stand: -9 ± 4% and ascend stairs: -4 ± 1%; p < 0.05) in all groups. For outcome variables representing ICF levels of body functions & structure and activity, there were no differences at baseline or improvements made between the groups after training. That said, with the exception of the domain of functional activity (reported 17 ± 34% improvement in the high-level burn cohort, p < 0.05), no changes were revealed in the participation level of ICF indexed by health-related quality of life questionnaires. These findings support the utilization of a 6-month unsupervised exercise training program in the long-term rehabilitation of individuals with burn injuries; that is, improvements in body functions & structure and activity can be achieved with an exercise regimen regardless of the severity of burn injury.